The Social Classes and Reflection of 18th Century Life in Novel Pamela - Dwi Adi Nugroho (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
In social life there are always rules, norms and values that organize the behavior or patterns of society. Yet some members of society cannot fulfill the rights and responsibilities in accordance with the norms and rules. Unequal rights and obligations in social life is the reason why there are social classes in society. It means that the people who have wealth and someone who can carry out many rights and obligations will be in the upper classes and those one with little or even no rights and responsibilities will be grouped in the lower classes. This research therefore aims to explain the phenomenon of social classes in the novel Pamela, and social condition in 18th century life in England that reflected in the novel. This research used descriptive  qualitative  method.  It was conducted by describing the data within literary work which were related to the topic of the research. The analysis of the data was done using sociology of literature approach put forward by Swingewood and Laurenson. The results of this research show that during England 18th century, social discrimination has become a major problem in the community. Social status become the standard of interaction in the society. Success and prestige of a person are measured based on his/her birth. Nobody wants to be at the bottom of the social hierarchy. The character of Pamela never think that money and power is everything. She never despise her identity as a lower class citizen who is always treated unequally in the society.